Trigonometry

Given the equation 2cos^2x+sinx-1=0

1. Explain why this equation cannot be factored.

2. Use a trigonometric identity to change the equation into one that can be factored.

1. 👍
2. 👎
3. 👁
1. can't be factored because different functions are involved.

As if you had y^2+x-1 = 0

But, using a well-known identity connecting sin and cos,

2cos^2 + sin - 1 = 0
2 - 2sin^2 + sin - 1 = 0
2sin^2 - sin - 1 = 0
(2sinx+1)(sinx-1) = 0

1. 👍
2. 👎

Similar Questions

1. Maths

Find the general solution of equation sinx + cosx = 2 (root2) (sinx)(cosx)

2. Trig.......

I need to prove that the following is true. Thanks (2tanx /1-tan^x)+(1/2cos^2x-1)= (cosx+sinx)/(cosx - sinx) and thanks ........... check your typing. I tried 30º, the two sides are not equal, they differ by 1 oh , thank you Mr

3. math

Find all solutions to the equation tan(t)=1/tan (t) in the interval 0

4. Algebra

What method(s) would you choose to solve the equation? Explain your reasoning. 4x^2-48=0 a. Quadratic formula, graphing; the equation cannot be factored easily since the numbers are large. Selected:b. Square roots; there is no

1. Calculus

Which of the following is a separable, first-order differential equation? A) dy/dx= x+y/2x B) dy/dx=x+y/x-y C) dy/dx=sinx

2. math;)

The equation 2sinx+sqrt(3)cotx=sinx is partially solved below. 2sinx+sqrt(3)cotx=sinx sinx(2sinx+sqrt(3)cotx)=sinx(sinx) 2sin^2x+sqrt(3)cosx=sin^2x sin^2x+sqrt(3)cosx=0 Which of the following steps could be included in the

3. Math

(sinx - cosx)(sinx + cosx) = 2sin^2x -1 I need some tips on trigonometric identities. Why shouldn't I just turn (sinx + cosx) into 1 and would it still have the same identity?

Which of the following are trigonometric identities? (Can be more then one answer) tanx cosx cscx = 1 secx-cosx/secs=sin^2x 1-tanxtany=cos(x+y)/cosxcosy 4cosx sinx = 2cosx + 1 - 2sinx Find all solutions to the equation cosx

1. Trig

Verify the identity: tanx(cos2x) = sin2x - tanx Left Side = (sinx/cosx)(2cos^2 x -1) =sinx(2cos^2 x - 1)/cosx Right Side = 2sinx cosx - sinx/cosx =(2sinxcos^2 x - sinx)/cosx =sinx(2cos^2 x -1)/cosx = L.S. Q.E.D.